BORROWING AND CLIPPING PROCESSES IN MINANGKABAU SONG: A MORPHOLOGICAL ANALYSIS - Naza Fanisa; Deliana Deliana (Jurnal Suluh Pendidikan, 2026)
This study investigates morphological processes, specifically clipping and borrowing in the Minangkabau traditional song Ayam Den Lapeh. Using a qualitative descriptive approach, the study identifies fifteen clipping forms and one borrowing. The analysis follows a structured sequence: research purpose, methodology, key findings, and implications. Findings reveal systematic morphological reduction aligned with Minangkabau phonotactic preferences, including the avoidance of consonant clusters and preference for open syllables. The borrowing biaro, originating from Sanskrit vihāra, reflects early cultural contact in the Malayic region. These results contribute to understanding morphological tendencies in oral traditions and support broader comparative studies of Malayic and Austronesian morphology